2019
DOI: 10.1039/c8ra10121c
|View full text |Cite
|
Sign up to set email alerts
|

Highly exfoliated montmorillonite clay reinforced thermoplastic polyurethane elastomer:in situpreparation and efficient strengthening

Abstract: Highly exfoliated montmorillonite (MMT) clay reinforced thermoplastic polyurethane elastomers (TPUs) were prepared by an in situ solution polymerization method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…An increase in the amount of clay from 1 to 5 wt.% was reported to increase the thermal stability of the TPU matrix from 12 to 34 • C, respectively [52]. The increase in thermal stability with an increase for MMT in the TPU matrix has also been reported in previous studies [56]. The improvement in thermal stability of the clay-TPU nanocomposite was found to be directly connected to the degree of dispersion of the nanoclay in the TPU matrix [89].…”
Section: Thermal Properties Of Nanofiller-tpu Nanocompositessupporting
confidence: 76%
See 3 more Smart Citations
“…An increase in the amount of clay from 1 to 5 wt.% was reported to increase the thermal stability of the TPU matrix from 12 to 34 • C, respectively [52]. The increase in thermal stability with an increase for MMT in the TPU matrix has also been reported in previous studies [56]. The improvement in thermal stability of the clay-TPU nanocomposite was found to be directly connected to the degree of dispersion of the nanoclay in the TPU matrix [89].…”
Section: Thermal Properties Of Nanofiller-tpu Nanocompositessupporting
confidence: 76%
“…However, modulus and tensile strength are increased by 110 and 160%, respectively, for the nanocomposite containing 5 wt.% of Cloisite ® 30B. The reaction of the surface [-OH] group of the MMT with the isocyanate during in situ synthesis, which leads to an improvement in tensile strength, as well as elongation at break, has been observed from experimentation [56].…”
Section: Mechanical Properties Of Nanofiller-tpu Nanocompositesmentioning
confidence: 85%
See 2 more Smart Citations
“…However, there were no obvious diffraction peaks found for OMMT/HBPA at 2θ = 2-10°. From literature, it was observed that if the MMT was completely exfoliated into individual and collapsed silicate layers, the regular crystalline structure cannot be found from the XRD patterns ( Ji et al 2017;Osman et al 2017;Xu et al 2019a). From Figure 1a, it was observed that there were some small peaks at 25°, 32°, and 34°.…”
Section: Characterization Of Ommt/hbpa Emulsionmentioning
confidence: 97%